2011
DOI: 10.1163/22941932-90000046
|View full text |Cite
|
Sign up to set email alerts
|

Wood Anatomy of Lecythidaceae Species called “Tauari”

Abstract: Woods from an important group of Lecythidaceae species called “tauari” can hardly be identified in the field by their gross and general features. In this study we show that, when properly delimited to the genera Allantoma, Cariniana and Couratari, wood anatomical characteristics can be used to identify the species known as “tauari”, even though it is not possible to separate all species. In addition to anatomical characters, wood colour is an important character to help distinguish species of Cariniana and All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In general, members of Lecythidaceae have reticulate axial parenchyma. This feature has been reported by other researchers of the genus Couratari (Mainieri & Chimelo 1989, Alves & Angyalossy-Alfonso 2002, Coradin et al 2010, Bernal et al 2011, Wheeler 2011.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In general, members of Lecythidaceae have reticulate axial parenchyma. This feature has been reported by other researchers of the genus Couratari (Mainieri & Chimelo 1989, Alves & Angyalossy-Alfonso 2002, Coradin et al 2010, Bernal et al 2011, Wheeler 2011.…”
Section: Resultssupporting
confidence: 84%
“…This arrangement is typical in other important timber species of Lecythidaceae, such as Allantoma lineata, Bertholletia excelsa, Cariniana micrantha and Lecythis pisonis(Coradin et al 2010). However, the genus Couratari differs from other Tauaris by the yellow color of the heartwood (Figure2-C2)(Bernal et al 2011).…”
mentioning
confidence: 99%
“…Likewise, some species of Manilkara and Pouteria have very similar wood anatomy, making their distinction impracticable (Santini Junior 2013). Bernal et al (2011) also reported difficulties distinguishing species referred to as ''Tauari'', and used differences in color and microscopic quantitative data to sort them. According to the list of species of the Brazilian Flora (Flora do Brasil 2020 under construction 2016), there are 18 species of Manilkara in Brazil, of which 15 are endemic, while there are 122 species of Pouteria, of which 52 are endemic.…”
Section: Resultsmentioning
confidence: 99%
“…Cariniana, Couratari, and Lecythis share most characters with the fossil. Cariniana and Couratari, which are very similar in anatomy (Bernal et al 2011), generally have rays 1-2(-3)-seriate but include taxa (Cariniana estrellensis (raddi) Kuntze, Couratari guianensis Aubl.) with wider rays (InsideWood 2004onwards).…”
Section: Lecythidaceaementioning
confidence: 99%